Mixed Problem for an Ultraparabolic Equation in Unbounded Domain - Lavrenyuk, S. P.; Protsakh, N. P. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We investigate a mixed problem for a nonlinear ultraparabolic equation in a certain domain Q unbounded in the space variables. This equation degenerates on a part of the lateral surface on which boundary conditions are given. We establish conditions for the existence and uniqueness of a solution of the mixed problem for the ultraparabolic equation; these conditions do not depend on the behavior of the solution at infinity. The problem is investigated in generalized Lebesgue spaces.